The effectiveness of the Investment climate in the athletic Sports Institution to attract Investment ( Afield study of the Directorate of youth and sport to Adrar ) - abdelkader.maksoud (sports creativity, 2025)
The present study aimed to know the effectiveness of the investment climate to attract investment in sporting institutions, we relied on descriptive and research sample consisted of 38 member of Enterprise Manager heads of interests and employees of the Directorate of youth and sport to Adrar where distribution Questionnaire on the topic of study which built his interlocutor among previous studies related to research topic. The study concluded that the various actions and policies as well as reindeer and granted for ongoing business and financial officers in addition to creating an environment that is accessible and fertile all at the disposal of those which confirms that the various conditions for the assignment of different investments and that will Strengthen and revitalize investment in sport at the local and national level in General and sports institutions in particular .